Multimodal Use of New Coumarin‐Based Fluorescent Chemosensors: Towards Highly Selective Optical Sensors for Hg2+ Probing. Issue 43 (11th September 2013) - Bazzicalupi, Carla; Caltagirone, Claudia; Cao, Zenfeng; Chen, Qibin; Di Natale, Corrado; Garau, Alessandra; Lippolis, Vito; Lvova, Larisa; Liu, Honglai; Lundström, Ingemar; Mostallino, M. Cristina; Nieddu, Mattia; et al.
Abstract Despite several types of fluorescent sensing molecules have been proposed and examined to signal Hg2+ ion binding, the development of fluorescence‐based devices for in‐field Hg2+ detection and screening in environmental and industrial samples is still a challenging task. Herein, we report the synthesis and characterization of three new coumarin‐based fluorescent chemosensors featuring mixed thia/aza macrocyclic framework as receptors units, that is, ligands L1–L3. These probes revealed an OFF–ON selective response to the presence of Hg2+ ions in MeCN/H2O 4:1 (v/v), which allowed imaging of this metal ion in Cos‐7 cells in vitro. Once included in silica core–polyethylene glycol (PEG) shell nanoparticles or supported on polyvinyl chloride (PVC)‐based polymeric membranes, ligands L1–L3 can also selectively sense Hg2+ ions in pure water. In particular we have developed an optical sensing array tacking advantage of the fluorescent properties of ligand L3 and based on the computer screen photo assisted technique (CSPT). In the device ligand L3 is dispersed into PVC membranes and it quantitatively responds to Hg2+ ions in natural water samples.